2022
DOI: 10.1186/s13075-022-02764-3
|View full text |Cite|
|
Sign up to set email alerts
|

Association of tramadol with all-cause mortality, cardiovascular diseases, venous thromboembolism, and hip fractures among patients with osteoarthritis: a population-based study

Abstract: Background The use of tramadol among osteoarthritis (OA) patients has been increasing rapidly around the world, but population-based studies on its safety profile among OA patients are scarce. We sought to determine if tramadol use in OA patients is associated with increased risks of all-cause mortality, cardiovascular diseases (CVD), venous thromboembolism (VTE), and hip fractures compared with commonly prescribed nonsteroidal anti-inflammatory drugs (NSAIDs) or codeine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
(45 reference statements)
1
15
0
Order By: Relevance
“…As for VTE, although opioid use disorders were associated with increased VTE risk, particularly postoperatively,39 40 there is very limited data on VTE risk with prescription opioids. One recent study comparing tramadol with different NSAIDs in patients with osteoarthritis found an increased risk of VTE with tramadol against diclofenac and cyclo-oxygenase-2 inhibitors 41. Like ours, the VTE risk increase with opioids was higher against nsNSAIDs as diclofenac than cyclo-oxygenase-2 inhibitors.…”
Section: Discussionsupporting
confidence: 67%
“…As for VTE, although opioid use disorders were associated with increased VTE risk, particularly postoperatively,39 40 there is very limited data on VTE risk with prescription opioids. One recent study comparing tramadol with different NSAIDs in patients with osteoarthritis found an increased risk of VTE with tramadol against diclofenac and cyclo-oxygenase-2 inhibitors 41. Like ours, the VTE risk increase with opioids was higher against nsNSAIDs as diclofenac than cyclo-oxygenase-2 inhibitors.…”
Section: Discussionsupporting
confidence: 67%
“…We conducted a sensitivity analysis to explore heterogeneity related to risk of bias. When studies scored as having a high risk of bias were removed (n = 5 studies) (46–48,67,69), the pooled prescribing estimate remained similar (43.8% [95% CI 36.8, 51.1], n = 46 studies, high quality of evidence I 2 = 5.1%) (11,12,25,26,28–46,49–56,58–61,58–64,65,66,68,70–73) compared to the original estimate with high heterogeneity (43.1% [95% CI 36.3, 50.1], n = 51 studies, I 2 = 99.9%, low quality of evidence). A post hoc sensitivity analysis was conducted to explore the primary analyses using an alternative statistical approach (see Supplementary Figure 1, available on the Arthritis Care & Research website at https://doi.org/10.1002/acr.25157), which resulted in less conservative estimates than our original model.…”
Section: Resultsmentioning
confidence: 98%
“…The included studies were published between 1989 and 2022 and were all in English except 1 study published in Croatian (56). Studies were from 31 countries across the globe, including South Asia (n = 4 studies) (37,47,49,57), Middle East and North Africa (n = 1 study) (33), East Asia and Pacific (n = 10 studies) (12,25,32,38,40,51,53,58–60), Europe and Central Asia (n = 23 studies) (26–29,39,42,43,45,46,48,50,52,54–56,61–68), Latin America and Caribbean (n = 1 study) (44), and North America (n = 12 studies) (11,30,31,34–36,41,69–73). Most studies (90.2%) were from high‐income countries with 1 study from an upper‐middle income country (44), and 4 studies were from lower‐middle income countries (37,47,49,57).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon publication of the original article [ 1 ], it was noticed that final sentence in the Abstract's Results section was incorrect. The correct sentence is: "No differences were observed between tramadol and codeine for all events."…”
mentioning
confidence: 99%